2005
DOI: 10.1093/ndt/gfi266
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from calcineurin inhibitors to sirolimus in chronic allograft dysfunction: changes in glomerular haemodynamics and proteinuria

Abstract: After conversion, P(G) shows a tendency to increase and RFR decreases significantly-characteristics of hyperfiltration, which could possibly partially explain the increase of proteinuria. Therefore, the application of angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers seems promising. To avoid hyperfiltration, conversion should be performed early when renal insufficiency is still moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 15 publications
2
49
0
3
Order By: Relevance
“…The mechanism by which the Tac/SRL combination is potentially more nephrotoxic is unclear. The mechanism implicated includes a complex cascade of events leading to perturbation of glomerular hemodynamics in the setting of Tac/SRL combination therapy (29).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which the Tac/SRL combination is potentially more nephrotoxic is unclear. The mechanism implicated includes a complex cascade of events leading to perturbation of glomerular hemodynamics in the setting of Tac/SRL combination therapy (29).…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria was reported to increase in renal transplant recipients with chronic allograft dysfunction who had been shifted to sirolimus treatment after withdrawal of a calcineurin inhibitor (27). Proteinuria was typically of glomerular origin (28) and could not be explained just by an increase in GFR associated with cyclosporin withdrawal (29). Finding that sirolimus exacerbated both proteinuria and different markers of podocyte damage in a model of severe puromycin-induced glomerular injury (30) can be taken to suggest that sirolimus may have a direct nephrotoxic effect, particularly in patients with advanced renal disease, such as our patients with ADPKD.…”
Section: Safetymentioning
confidence: 99%
“…Ducloux et al (17) reported that in 31 renal transplant recipients whose cyclosporine (CsA) was withdrawn because of cyclosporine toxicity or CAN, baseline proteinuria was 0.79 Ϯ 0.6 g/d and increased to 1.79 Ϯ 0.8 g/d 24 mo after CsA withdrawal. Because CNI reduce renal blood flow, CNI withdrawal may reveal existing CAN lesions that result in proteinuria, and an increase in intraglomerular pressure has been described after the switch (3,5,18).…”
Section: Sirolimus-induced Proteinuria and Glomerular Lesionsmentioning
confidence: 99%